EPEN-15. RETINOIDS AS POTENTIAL CHEMOTHERAPEUTIC OPTIONS FOR POSTERIOR FOSSA EPENDYMOMA OF CHILDHOOD - Amani, Vladimir (Neuro Oncol, 2018)
Chemotherapy has yet to show reproducible therapeutic benefit in ependymoma, and this is partly due to a lack of models for preclinical testing. Treatment of ependymoma has changed little over the last 40 years and is essentially limited to surgery and radiation. Our group has published establishing 2 posterior fossa 1q+ ependymoma cell lines which provides a model for high throughput testing of therapeutic treatments. With the goal of immediate clinical translation, we screened these cell lines for ependymoma-selective drug sensitivity across a panel of 124 FDA-approved oncology drugs. Treatment effect was measured using a tritiated-thymidine incorporation proliferation assay and ependymoma-selective sensitivity was determined by comparison to a panel of other pediatric brain tumor types (medulloblastoma, glioblastoma, DIPG and AT/RT). Upon screening we identified retinoids bexarotene, tretinoin and isotretinoin as effective and ependymoma-selective. Retinoid Acid Receptors alpha and beta (RARɑ and RARβ) and Retinoid X Receptor alpha (RXRɑ) were overexpressed in cell lines and primary samples versus other pediatric brain tumors and normal brain. We examined the effect of retinoids on ependymoma using transcriptomic analysis which revealed Retinoic Acid Receptor Responder 1 (RARRES1) as the most upregulated gene in bexarotene-treated EPN cell lines. RARRES1 is a known tumor suppressor gene described in a variety of human cancers and has been shown to repress mitogen-activated protein kinase (MAPK) activation. We aim to further investigate the mechanism by which retinoids inhibit ependymoma cell growth. These findings may support further clinical evaluation of retinoids as effective chemotherapeutics for ependymoma.